Informasi Kesehatan melalui Penyuluhan, Poster dan Leaflet di Dusun Talang Parit Desa Kemingking Dalam Kecamatan Taman Rajo Provinsi Jambi - Yulianis Yulianis; Ayu Ulil Fauziah; Diah Kusumawati (Jurnal Abdimas Kesehatan (JAK), 2020)
AbstractTalang Parit Hamlet Kemingking Dalam Village is one of the Villages located in Taman Rajo Sub-District, Muaro Jambi District, where most of its residents work as factory laborers and gardeners. Gastritis, Gout and Hypertension are the 3 biggest diseases in RT.09 Talang Parit Hamlet, Kemingking Dalam Village. Therefore, health counseling was conducted to the community RT.09 Talang Parit Hamlet related to gastritis, gout, and hypertension. Health education is one way that can be used to convey health information. Health counseling can be done in two ways, which can be directly (face to face) and indirectly (mass media). This activity aims to increase public knowledge about diseases including symptoms, prevention and treatment, to increase public knowledge about natural resources that can be processed to overcome some diseases and about the classification of drugs, and to overcome errors in the use of drugs. This activity uses the method of providing information through direct media, namely counseling and indirectly using posters and leaflets. Respondents involved were 36 adults and parents. The results of this outreach activity indicate that there is an influence of health education before and after on the level of community knowledge